In-Cave Wireless Communication System - Yavuz, A. Gokhan; Taysi, Z. Cihan; Celik, Esra (IEEE COMPUTER SOC, 2009)
Usually wireless communication is preferred to wired communication within caves considering the known difficulties of laying wires and related equipment in such rugged environments. Nevertheless both the inner structures of the caves and RF challenging conditions within the caves make the use of wireless solutions, like walkie-talkies or CB radios, deficient. In this paper, we propose a Wireless Multimedia Sensor Network (WMSN) based communication architecture which can guarantee a desired level of uninterrupted connectivity and communication quality. Our proposed system, which is called In-Cave Wireless Communication System (ICWCS), consists of backbone nodes and mobile nodes which design is based on our previous general purpose wireless sensor node VF1A[4]. Backbone nodes are basically responsible for the connectivity within the ICWCS network, whereas mobile nodes have similar functionality like cellular phones. ICWCS provides reliable and efficient communication within caves.
Keywords: In cave communication; wireless multimedia sensor networks; wireless multimedia sensors; voice streaming; voice over sensor network; VOICE; Computer Science; Telecommunications